PENYULUHAN INOVASI PENGEMASAN PRODUK USAHA DARING PADA KOMUNITAS WIRAUSAHA CARIMITRABISNIS SURAKARTA - Belligo Agra (Universitas 'Aisyiyah Surakarta, 2021)
During the Covid-19 pandemic, many MSMEs experienced a decline in sales. One of the main problems is the shift in consumer shopping styles to online shopping and the decline in consumer buying interest. The solution offered for this problem is packaging innovation and product design. This community service aims to provide counseling and assistance to partners regarding packaging innovation and product design. This community service partner is the Carimitrabisnis entrepreneurial community. This community consists of 35 entrepreneurs from various business fields in Surakarta. The expected outcome of this community service activity is for partners to gain knowledge about the importance of trademark design, packaging, and direction to partners in terms of promotion through the internet to increase the number of sales.